Can Competition Reduce Quality? - Kurt R. Brekke; Luigi Siciliani; Odd Rune Straume (Center for Economic Studies and ifo Institute (CESifo), 2014)
In a spatial competition setting there is usually a non-negative relationship between competition and quality. In this paper we offer a novel mechanism whereby competition leads to lower quality. This mechanism relies on two key assumptions, namely that the providers are motivated and risk-averse. We show that the negative relationship between competition and quality is robust to any given number of firms in the market and whether quality and price decisions are simultaneous or sequential. We also show that competition may improve social welfare despite the adverse effect on quality. Our proposed mechanism can help explain empirical findings of a negative effect of competition on quality in markets such as health care, long-term care, and higher education.
Keywords: D21; D43; L13; L30; 330; quality and price competition; motivated providers; risk-averse providers